Pemberdayaan Ibu Pengajian Sebagai Upaya Pencegahan Kanker Serviks di Kota Medan - Siti Mirhalina; Humairah Medina Liza Lubis; Emni Purwoningsih (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2020)
According to Riskesdas data in 2013 in Indonesia, it is estimated that 40,000 new cases of cervical cancer are found each year. The incidence of cancer sufferers continues to increase and requires immediate treatment to prevent the continued increase in cancer death rates. This can be achieved, one of which is the right detection of cancer, both diagnosis and prognosis. The objectives of this community service are: (1) Finding cervical cancer cases that become an iceberg phenomenon and undetectable at an early stage, (2) Providing debriefing about Pap smear screening programs in Medan that do not run routinely or are not even carried out (3 ) Providing information on the importance of Pap smears in women of reproductive age,  (4) Empowering cadres in this case the members of the Istiqomah Mosque study in each neighborhood in Pahlawan Village as a system of coordination in treating cervical cancer in their respective work areas. Of the 30 people who had Pap smear tests, none of them found suspicious results, only in the form of inflammation of the cervix which could be treated with antibiotics. Keywords: members of Istiqomah mosque, prevention, cervical cancer